Digital Supply Chain Model for Humanitarian Management in Thailand - Artaphon Chansamut (ExcelingTech, 2023)
The purpose of paper were to study and to evaluate digital supply chain model for humanitarian management in Thailand. The samples in the research study consisted of ten purposively selected experts consisted of ten experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model eight elements namely main components, Donors, Beneficiaries, Suppliers , Humanitarian organizations, Consumers aid Recipients Satisfaction and Feedback. The ten experts agree that digital supply chain model for humanitarian management in Thailand was high suitability that mean digital supply chain model for humanitarian management in Thailand to may be appropriately applied in support the tasks.